Expression of iron metabolism-related genes is altered in Familial Hypercholesterolemia patients - Mateus, Ana (2013)
Atherosclerosis (ATH) is the major cause of cardiovascular diseases (CVD) causing great morbidity and mortality. Typically, ATH develops and progresses silently for years, without symptoms. Familial Hypercholesterolemia (FH) is an autosomal genetic disorder characterized by high levels of total and LDL cholesterol, a familial history of hypercholesterolemia and premature ATH. Atherogenesis is characterized by an early deposition of LDL in the artery walls, leading to the recruitment and activation of peripheral blood mononuclear cells (PBMC) to the plaque. In addition, monocyte-derived macrophages accumulate oxidized LDL and differentiate into foam cells, leading to the development of complex and unstable lesions. The oxidative modification of LDL, accelerated, or even initiated by transition metals as iron (Fe) has been implicated as an early step in the formation of atheromatous lesions.